Ideal Hajj Pilgrim Airplane Seat Configuration Based on Health Condition Priority - Issalillah, Fayola; Griana, Tias Pramesti (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 2 (2024): Proceeding Annual Symposium on Hajj and Umrah MedicineDO - 10.18860/anshar.v2i0.3233, 2024)
The Hajj pilgrimage become one of the largest religious mass gatherings involving millions of pilgrims every year. The main challenge of hajj is taking care health pilgrims, especially during long flights. This study analyzed airplane seat configuration for hajj pilgrims based on health condition priorities. This case report uses analytical observational methods on a Surabaya debarkation batch of Indonesian Hajj pilgrims in 2024. Problem analysis supported by relevant secondary data. The results show that the ideal seat configuration needs to take into account several factors, such as health pilgrims conditions before the flight and accessibility for pilgrims with disabilities, the elderly, and those under observation. This will divide into several processes. The pre-flight step involves determination pilgrims airworthiness and grouping them according to health conditions. In-flight step is positioning each pilgrims on board based on the layout of passenger accommodation with the mobility flow according to first in-first out. Post-flight step consists of sustainable monitoring and evaluation to develop a better system. Therefore, seats configuration of the Hajj pilgrims on the plane based on their health status is a step critical to ensure their safety and comfort during the flight.